Succession from bog pine (Pinus uncinata var. rotundata) to Norway spruce (Picea abies) stands in relation to anthropic factors in Les Saignolis bog, Jura Mountains, Switzerland - Freléchoux, François; Buttler, Alexandre; Gillet, François; Gobat, Jean-Michel; Schweingruber, Fritz (My University, 2003)
In Jura bogs, on deep and nutrient-poor peat, the ecotone between bog pine forest and Norway spruce forest is sharp and, in a few disturbed situations, no succession pine forest-spruce forest occurs. The bog Les Saignolis lies at the top of an anticline, on thin and oligotrophic peat. Several documents attest some anthropic disturbances (clear cut and drainage). Beside these historical data and with the aim of reconstructing vegetation dynamics and tree growth, we realised synusial phytosociological releves and, in a mixed pine-spruce stand, we studied tree radial growth. Following the clear cut, the bog pine, the pubescent birch, and the Norway spruce settled simultaneously. The birch disappeared rapidly. The present cohort of pine settled and grew rapidly, and then declined because of the competition by spruce. Spruce settled progressively and increased its growth regularly except when pine settled and grew. Interspecific competition between pines and spruces and intraspecific competition between dominant and sub-dominant spruces were put into evidence by radial growth analysis.
Keywords: raised bog; disturbance; succession; dendroecology; synusial; phytosociology; LODGEPOLE PINE; SITKA SPRUCE; TREE ROOTS; WATER-TABLE; SYNUSIAL; PHYTOSOCIOLOGY; OXYGEN-TRANSPORT; ANNOTATED LIST; TOLERANCE; GROWTH; DEPTH